The 8th Habit, From Effectiveness to Greatness - Covey, Stephen R. (London Simon & Schuster, 2007)
The most recent major title from Stephen R. Covey, author of the 15-million-copy bestseller THE 7 HABITS OF HIGHLY EFFECTIVE PEOPLE, now in handy B-format edition
Keywords: Self-actualization (Psychology) -- Success -- Satisfaction